ABOUT APPLICATION OF GEOINFORMATION IN THE EDUCATIONSYSTEM AND COMMUNICATION OBJECTS OF THE STATE CADASTR - ALLALLAZAROV O.R.; SAFAROVE.YU.; PRENOV SH.M. (International Journal of Innovations in Engineering Research and Technology, 2021)
The article describes the content of the organizationof geoinformatics and GIS technologies;establishment; communication of cadastr and its use in educational system; the content ofnew “Geoinformatics” educational literature in masters outlined.